Crystalline Insulators: Length Scale and Dimensionality of Defects in Epitaxial SnTe Topological Crystalline Insulator Films (Adv. Mater. Interfaces 2/2017). Issue 2 (January 2017) - Dagdeviren, Omur E.; Zhou, Chao; Zou, Ke; Simon, Georg H.; Albright, Stephen D.; Mandal, Subhasish; Morales‐Acosta, Mayra D.; Zhu, Xiaodong; Ismail‐Beigi, Sohrab; Walker, Frederick J.; Ahn, Charles H.; Schwarz, Udo D.; et al.
Abstract : The surface states of topological crystalline insulators (TCIs) are protected by crystal symmetry, suggesting that symmetry breaking surface defects may be used to tailor the surface states. Eric I. Altman and co‐workers show that the epitaxial growth of a TCI creates such defects which modulate the surface electronic properties over mesoscopic and atomic scales in article 1601011.